Ankle Arthrodesis: Epidemiology, Etiology, and Complications in Diabetic vs Nondiabetic Patients Using US Nationwide Inpatient Sample Data - Assil Mahamid MD; David Maman MD; Summer Sofer; Mykhail Pavlenko MD; Amr Mansour MD; Marah Hodruj MD; Yaron Berkovich MD; Eyal Behrbalk MD (Foot & Ankle Orthopaedics)
Background: Ankle arthrodesis (AA), or ankle fusion, is a surgical procedure used to treat severe ankle pathologies, particularly in patients with chronic pain and reduced mobility due to conditions like osteoarthritis, posttraumatic arthritis, and Charcot arthropathy. Diabetic patients undergoing AA often face higher risks of complications due to comorbidities such as dyslipidemia and hypertension. This study aims to compare the outcomes of AA in diabetic vs nondiabetic patients, using data from the Nationwide Inpatient Sample (NIS) from 2016 to 2019. Methods: Using the Nationwide Inpatient Sample database, 12 325 patients who underwent ankle arthrodesis were identified from 2016 to 2019 based on ICD-10 procedure codes. χ 2 tests and t tests were used for univariate analysis, followed by multivariate logistic regression to assess complications between diabetic and nondiabetic patients. Temporal trends in surgical volume were analyzed using linear regression models, and risk ratios were calculated for perioperative complications during the index hospital stay. Results: Primary osteoarthritis was the most common cause, accounting for 55.4% of AA procedures. Multivariate logistic regression revealed that diabetes mellitus (DM) was significantly associated with increased risks of blood loss (odds ratio [OR] 1.59, 95% CI 1.23-2.05, P = .004), infection (OR 3.12, 95% CI 2.55-3.82, P < .001), heart failure (OR 1.35, 95% CI 1.06-1.73, P = .01), and acute kidney injury (OR 2.42, 95% CI 1.57-3.75, P = .001). No significant association was observed between DM and pneumonia (OR 2.27, 95% CI 1.645-4.605, P = .20). Conclusion: Diabetic patients undergoing AA have higher rates of comorbidities and postoperative complications, leading to longer hospital stays. These findings highlight the need for comprehensive preoperative and postoperative care to improve outcomes in this population. Level of Evidence: Level III, retrospective study.